Genetics in parkinson’s disease: From better disease understanding to machine learning based precision medicine - Aborageh, Mohamed; Krawitz, Peter; Fröhlich, Holger (Frontiers in Molecular Medicine, 2022)
Parkinson’s Disease (PD) is a neurodegenerative disorder with highly heterogeneous phenotypes. Accordingly, it has been challenging to robustly identify genetic factors associated with disease risk, prognosis and therapy response via genome-wide association studies (GWAS). In this review we first provide an overview of existing statistical methods to detect associations between genetic variants and the disease phenotypes in existing PD GWAS. Secondly, we discuss the potential of machine learning approaches to better quantify disease phenotypes and to move beyond disease understanding towards a better-personalized treatment of the disease.